The bride - Sidhwa, Bapsi; Hussein, Aamer (ILQA Publications, and imprint of Reading Lahore, 2013)
"The Bride" is a captivating story that explores themes of love, tradition, and transformation as a young woman embarks on a life-changing journey through marriage.